PROBLEMS OF FREEDOM OF CONSCIENCE (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The article analyzes the strengthening of democratic guarantees of citizens’ rights and freedoms based on the principles of social justice and constitutional reforms in the Republic of Uzbekistan. The Government of Uzbekistan aims to regulate citizens’ religious freedoms through the improvement of the Law “On Freedom of Conscience and Religious Organizations.”